1998
DOI: 10.1037/0278-7393.24.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Aging, optimal testing times, and negative priming.

Abstract: The effects of time-of-day preferences on selective attention were tested in 2 experiments after normative work with 975 younger adults and 143 older adults verified C. P. May, L. Hasher, and E. R. finding that most older adults prefer the morning, whereas younger adults prefer activities later in the day. In Experiment 1, the cognitive effects of testing at preferred or nonpreferred times of day were examined in negative priming and related paradigms because (a) older adults typically have not shown negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
60
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 82 publications
10
60
4
Order By: Relevance
“…This pattern of findings is also consistent with emerging reports (e.g., Intons-Peterson et al, 1998;Petros et al, 1990;Yoon et al, 1998) that individual and age-related differences in circadian arousal patterns are nontrivial contributors to cognitive performance across the day.…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of findings is also consistent with emerging reports (e.g., Intons-Peterson et al, 1998;Petros et al, 1990;Yoon et al, 1998) that individual and age-related differences in circadian arousal patterns are nontrivial contributors to cognitive performance across the day.…”
Section: Discussionsupporting
confidence: 91%
“…The subjects of these studies were mostly young, a population with a greater tendency to being afternoon types (13,14). In this case, it could be suggested that the better performance of individuals who trained in the afternoon was a result of a synchronic effect and not related to training time-of-day (13)(14)(15). However, even when the chronotype variable was controlled, the result was the same.…”
Section: Discussionmentioning
confidence: 54%
“…The subjects who acquired information in the afternoon performed better, even though one-third of the sample consisted of subjects classified as morning types. A plausible explanation for this result is that most studies that show an interaction between chronotype and cognitive task time-of-day applied memory tests with a short interval between training and the test (13)(14)(15). Perhaps, previously consolidated Data are reported as mean ± SEM of performance (hits minus errors).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific evidence for such claims is limited and typically ignores the potential importance of the synchrony between an individual's time of day preference, or 'chronotype,' and the time at which cognitive operations are performed. This is likely nontrivial because recent research with adults suggests that performance on a number of school relevant tasks (such as attention and memory) varies in synchrony with chronotype, with better performance in the morning than later in the day for Morning-types and better performance later in the day than in the morning for Evening-types (e.g., Hasher, Goldstein, & May, 2005;Intons-Peterson, Rocchi, West, McLellan, & Hackney, 1998;May, 1999;Yoon, May, Goldstein, & Hasher, in press). …”
Section: Introductionmentioning
confidence: 99%